2021
DOI: 10.4102/hts.v77i4.6655
|View full text |Cite
|
Sign up to set email alerts
|

A study of the role of Islamic spirituality in happiness of Muslim citizens

Abstract: Recreation and joy are considered as the basic needs of humans. When the human body and soul get tired, they yearn refreshment through various means. Since the primary goal of Islam is true perfection of humans and achieving higher meaning and purpose in life, the happiness emphasised in this school of thought must be such that it does not conflict with the goal of creation and the ultimate perfection of humans. Therefore, this study aimed to determine the role of Islamic spirituality in the happiness of 5000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…Furthermore, there is an association between spirituality and happiness. This finding follows those of previous studies, which have shown a similar relationship (Amiruddin et al, 2021;David et al, 2022;Mahipalan & Sheena, 2019a). Spirituality in a person can be associated with positive life functioning (Moal-Ulvoas, 2017).…”
Section: │ 271supporting
confidence: 91%
“…Furthermore, there is an association between spirituality and happiness. This finding follows those of previous studies, which have shown a similar relationship (Amiruddin et al, 2021;David et al, 2022;Mahipalan & Sheena, 2019a). Spirituality in a person can be associated with positive life functioning (Moal-Ulvoas, 2017).…”
Section: │ 271supporting
confidence: 91%
“…Particularly in the context of Muslim society, the religiosity of a Muslim determines their consumption behaviour, such as their acceptance of products from other cultures (Bukhari et al , 2019; Setyobudi et al , 2016); Muslim consumers may accept foreign product information or messages that do not contradict their beliefs and religious values (Bukhari et al , 2019; Setyobudi et al , 2016, 2015; Wilson and Ayad, 2021; Wilson and Grant, 2013; Wilson and Liu, 2011). Islamic teachings and principles are constructive, full of peace, perfection and centred on people’s welfare and well-being (Huda et al , 2019; Joshanloo and Weijers, 2019; Amiruddin et al , 2021). The environment is characterised by ethics, purity, humility and sincerity (Naz et al , 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hasil Penelitian ini didukung oleh penelitian (Misbah et al, 2015) yang menyatakan bahwa inflasi tidak berpengaruh terhadap perubahan laba operasional. Sedangkan berbeda dengan penelitian (Amiruddin et al, 2021) dan Azhariyah Khairunnisa yang mengatakan bahwa inflasi berpengaruh terhadap laba operasional.…”
Section: Pengaruh Inflasi Terhadap Perubahan Laba Operasional Bank Um...unclassified